Implementation of the Tahqiq Method in Learning the Qur'an at the Nurul Ummah International Madrasah - Rahmat, Rahmat; Yunas, Novy Setia; Fachrurazi, Fachrurazi (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
The Qur'an, as the holy book of Muslims, is strongly believed to contain teachings that bring truth, give good news, and remind of the threat of Allah SWT for His servants who deny the provisions of sharia. As a divine word, reading the Qur'an will get rewards, studying, practicing and even listening to people who are reading its verses will be rewarded by Allah SWT. This study aims to obtain complete data related to 1) Implementation of the Tahqiq method in learning the Qur'an at the Nurul Ummah Pacet Mojokerto International Standard Madrasah and 2) Implications of the Tahqiq method in learning the Qur'an at the Nurul Ummah Pacet Mojokerto International Standard Madrasah. To obtain complete data, this study utilized a qualitative research type with a case study approach, while the results of this study were obtained, 1) In its implementation, Tahqiq becomes a method in learning the Qur'an, and 2) As an implication of the implementation of the Tahqiq method, a) Tahqiq is widely interpreted as a method in strengthening the explanation of the general religious studies of the boarding school caretakers, which in practice after the Maghrib prayer, students attend general religious studies in the mosque then before the Isya prayer they enter a class called Tahqiq, and b) The Tahqiq method emphasizes the direction of the morning assembly at the Nurul Ummah International Standard Madrasah to ensure students' understanding of the direction of the assembly before they continue to school learning as it should.